Importance of the lateral parabrachial nucleus to sodium balance in fluid-depleted rats - Cabral, K. A.; Andrade, C. A.F. [UNESP] (Elsevier, 2016)
The lateral parabrachial nucleus (LPBN) exerts an important inhibitory influence for the control of sodium and water intake. However, the importance of LPBN on renal responses and cardiovascular changes during extracellular dehydration are still unknown. Here we investigated the effects of bilateral injections of moxonidine (alpha2-adrenergic and imidazoline receptor agonist) on renal and cardiovascular changes in fluid-depleted rats. Male Wistar rats (n = 4–8 per group) with bilateral stainless steel guide-cannulas implanted into the LPBN were treated with subcutaneous furosemide (10 mg/kg) + captopril (5 mg/kg) to induce fluid depletion. Forty-five min later vehicle or moxonidine (0.5 nmol/0.2 μl) were bilaterally injected into the LPBN. In fluid-depleted rats, moxonidine produced strong 0.3 M NaCl and water intake without noticeable changes in cardiovascular parameters. Moxonidine did not change sodium excretion (488 ± 135, vs. vehicle: 376 ± 75 μEq/1 h) or urinary volume (2.5 ± 0.7, vs. vehicle: 2.5 ± 0.3 ml/1 h) in fluid-depleted rats without access to fluids for rehydration. However, moxonidine decreased natriuresis (462 ± 127, vs. vehicle: 888 ± 122 μEq/1 h) and diuresis (2.5 ± 0.5, vs. vehicle: 4.5 ± 0.5 ml/1 h) in fluid-depleted rats submitted to i.g. rehydration. These data suggest that alpha2-adrenergic mechanism of the LPBN facilitates sodium/water retention and body fluid volume expansion during extracellular dehydration.
Keywords: Alpha2-adrenoceptor; Dehydration; Hindbrain; Natriuresis; Sodium